Phase behavior study on gas hydrates formation in gas dominant multiphase pipelines with crude oil and high CO2 mixed gas - Sayani, J.K.S. (Nature Research, 2020)
This research is focused on understanding the phase behavior of gas hydrate formation in the gas dominant multiphase pipelines containing mixed gas with high CO2, crude oil, and deionized water. The experimental conditions are in the pressure range of 3â7Â MPa with water cut as 20 of the volume. Initially, the effect of high CO2 content in natural gas on the phase boundary conditions of hydrates is studied through simulation (CSMGEM software) and experiments. Later, an additional phase of crude oil was introduced, with 15 of the volume to study the multiphase system. From the experimental analysis, thermodynamic equilibrium conditions were found, and the hydrate-liquidâvapor-equilibrium (HLVE) curves were drawn. The phase behavior is comprehended by comparing the HLVE curves of pure and multiphase systems. It is found that the high CO2 content tends to promote the gas hydrate formation. Based on the results, temperature variance and enthalpy of formation were calculated for the multiphase system. With a difference of 1.32 average temperature variance, the multiphase system exhibits inhibition. A basic statistical regression model was made to predict the gas hydrate formation in multiphase transmission pipelines. This work helps in understanding the effect of a new phase on gas hydrate formation. Â© 2020, The Author(s).